Health Spending and Political Influence: The Case of Earmarks and Health Care Facilities. (March 2015) - Leider, Jonathon P.; Tung, Greg; Castrucci, Brian; Sprague, James B.
Abstract : Earmarks, otherwise known as Congressionally directed spending requests, are a historically significant means of political influence over budgets. In this brief, we report on the results of a longitudinal study of federal earmarks affecting health care facilities and public health. We analyzed 10 years of earmark for health care facilities and examined the correlates of being in the top 50% of earmark recipients for each year. Having representatives or senators serving on the respective Appropriations committees were shown to have increased odds of being a top earmark recipient, as was being in jurisdictions with greater poverty. However, health-related measures of need were not significantly associated with being a top earmark recipient. Abstract : Supplemental Digital Content is Available in the Text.This article reports on the results of a longitudinal study of federal earmarks, by analyzing 10 years of earmark data, affecting health care and public health.